Development of banana (Musa sapientum var lacatan) jam - Inarsolin, Rona Burgos (2005.)
The study involved the development of banana jam using lacatan variety.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana; Musa sapientum var lacatan; Jam